Structural Characteristics of Dongxia Coal Mine Face Based on Radio and Channel Wave Seismic Exploration - Liu, Hongli; Chen, Jie; Yang, Genfa; Guo, Keying; Wang, Kai; Lv, Hongfeng; Da, Guozhi; Liu, Deqiang; Zhu, Tong; Shi, Dongrui (International Journal of Natural Resources and Environmental Studies, 2025)
Geological anomalies in underground coal seams pose serious risks to mining safety and productivity. This study applies an integrated geophysical approach—combining radio wave imaging and channel wave seismic methods—to investigate the structural integrity of the 31123-1 working face at Dongxia Coal Mine, China. Radio wave results indicated stable field intensities and low absorption coefficients, suggesting overall seam continuity with minor localized anomalies. Subsequent channel wave surveys confirmed the absence of faults or collapse features and identified a broad synclinal structure as the only significant anomaly. The findings demonstrate that integrating electromagnetic and seismic techniques enhances structural resolution and provides a reliable basis for safe and efficient mine planning in complex geological settings.